2020
DOI: 10.1096/fj.202000167rr
|View full text |Cite
|
Sign up to set email alerts
|

Brain iron deficiency and affected contextual fear memory in mice with conditional Ferroportin1 ablation in the brain

Abstract: Fear memory is a pivotal biological function by which organisms can predict possible danger to avoid or reduce harm. However, dysregulation of fear memory processing may lead to pathological fear or anxiety and produce serious clinical symptoms, such as post-traumatic stress disorder (PTSD). Iron deficiency (ID) is reported to inhibit the initiation of fear memory. In our study, we found that ferroportin1 (FPN1), the only known cellular iron export protein in mammals, and ablation in neurons and astrocytes cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…FPN1 is the only protein known to export cellular iron in mammals. 28 Conditional knockout of FPN1 in cerebral microvascular endothelial cells ( Fpn1 Cdh5 ‐cKO) inhibits the transport of peripheral iron into the brain through the blood–brain barrier (BBB), leading to brain iron deficiency. 20 FtH and FtL are cellular iron storage proteins that are usually used as indicators of uncommitted iron levels.…”
Section: Resultsmentioning
confidence: 99%
“…FPN1 is the only protein known to export cellular iron in mammals. 28 Conditional knockout of FPN1 in cerebral microvascular endothelial cells ( Fpn1 Cdh5 ‐cKO) inhibits the transport of peripheral iron into the brain through the blood–brain barrier (BBB), leading to brain iron deficiency. 20 FtH and FtL are cellular iron storage proteins that are usually used as indicators of uncommitted iron levels.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of brain iron homeostasis have highlighted the role of iron deficiency in memory formation. Knocking out the cellular iron export protein, ferroportin1, induces iron deficiency in neurons in cortex and hippocampus, which negatively affects the formation of fear memory and the contextual fear response in mice [34] . Iron deficiency in foetal and early postnatal life also affects brain growth and development.…”
Section: Resultsmentioning
confidence: 99%
“…Knocking out the cellular iron export protein, ferroportin1, induces iron deficiency in neurons in cortex and hippocampus, which negatively affects the formation of fear memory and the contextual fear response in mice. [34] Iron deficiency in foetal and early postnatal life also affects brain growth and development. For example, children with iron deficiency during early development have slower and smaller neurological and behavioural responses, despite subsequent treatment with adequate iron for 10 years.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…In addition, we also found incomplete knockout of Ccdc134 after crossing with Nestin-Cre mice. Other studies also showed that there were incomplete knockout of targeted molecules using Nestincre driver, such as TCTP and Fpn1, 40,41 suggesting that Nestin-cre driver targeting neural stem and progenitor cells, might lead to a significant decrease in the expression of targeted molecules in neuronal cells of cKO mice but not reach complete gene knockout.…”
Section: Discussionmentioning
confidence: 99%